Earnings Trajectories After Divorce: The Legacies of the Earner Model During Marriage - Daniel Brüggmann; Michaela Kreyenfeld (Population Research and Policy Review, 2023)
Divorce marks the legal endpoint of a marital union. While divorce is increasingly seen as a 'clean break', the past marital history of the couple may nevertheless shape their present conditions. In particular, there may be a legacy of a highly gendered division of labour during marriage that may affect the ex-spouses' earning trajectories beyond the date of divorce. Using register data from the German Pension Fund, we examine the earning trajectories of heterosexual couples who filed for a divorce in 2013 (24,616 men and 24,616 women). Using fixed-effects and matching techniques, we compare the earning trajectories of divorcees with those of a control group of married persons in the period spanning two years before and two years after divorce. In particular, we examine how the earner models divorcees followed during marriage shaped their future earning trajectories. Our results show that, on average, the earnings of a divorced woman in a male breadwinner constellation increased after divorce, while the earnings of her male ex-spouse declined. Nevertheless, large gender differences in earnings persisted: 2~years after separation, a divorced woman who had been in a male breadwinner constellation was, on average, earning 72% less than her ex-spouse. We discuss our findings against the background of recent policy reforms in Germany, which assume that ex-partners should be economically 'self-reliant' after divorce.
Keywords: 300; Divorce; Employment; Fixed-effects; Earnings; Germany; Matching